Kunst & Zwalm. - Pas, Johan; Soler, Eduardo Pérez; Biennale Zwalm 2003 (Zwalm : VZW Boem, 2003)
Banal, Isabel ; Canudas, Jordi ; Claeyé, Catherine ; Cloet, Marc ; Dardanyà, Pep ; De Decker, Koen ; De Leener, Eva ; Deceuninck, Damien ; Decuyper, Inge ; Denys, Francis ; et al.
Kunst & Zwalm, Zwalmstreek, augustus - september 2003
kunstcatalogus
Keywords: Zwalm